The imprint of childhood adversity on emotional processing in high functioning young adults. Issue 3 (30th October 2020) - Mirman, Aron; Bick, Atira S.; Kalla, Carmel; Canetti, Laura; Segman, Ronen; Dan, Rotem; Ben Yehuda, Ariel; Levin, Netta; Bonne, Omer
Abstract: Adverse childhood experiences (ACEs) have been acknowledged as risk factors for increased mental health complications in adulthood, specifically increasing susceptibility to developing psychopathology upon exposure to trauma. Yet, little is known regarding the impact of mild ACEs on highly functioning population. In this study forty participants were selected from a group of 366 highly selected military parachute trainees using the self‐report "childhood trauma questionnaire, " and classified into two groups of 20 each, with and without ACEs. Behavioral measurements were obtained before and at the peak of an intensive combat training period, including anxiety, depression and executive function assessment. Functional MRI including a negative emotional face perception task was conducted at the first time point. Psychometric and cognitive measurements revealed higher levels of anxiety and depressive symptoms, and more difficulties in executive functioning in the ACE group at baseline. Slower reaction time to emotional faces presentation was found in the ACE group. Lower activation in response to negative emotional faces stimuli was found in this group in bilateral secondary visual areas, left anterior insula, left parietal cortex and left primary motor and sensory regions. In contrast, higher activation in the ACE group was found in the right ventral lateral prefrontal cortex (Vlpfc). No significant differences between groups were detected in the amygdala. To conclude, mild adverse childhood experiences produce long‐term sequela on psychological wellbeing and neurocircuitry even in high functioning population. Brain regions modulated by childhood trauma may instigate avoidance mechanisms dampening the emotional and cognitive effects of intensive stress. Abstract : We investigated the impact of mild childhood adversity on high functioning young adults. Our study demonstrates the negative effect of childhood adversity on behavior emotion and cognitive function of highly selected healthy combat unit volunteers, as well as brain activity differences. We suggestthe brain modulates presenting reduced activation in perceptual and emotional related areas and relatively enhanced activation in inhibitory related areas when processing negative faces, to be part of an allegedly adaptive avoidance coping style.